2009
DOI: 10.1002/clc.20677
|View full text |Cite
|
Sign up to set email alerts
|

Is Right Ventricular Outflow Tract Pacing Superior to Right Ventricular Apex Pacing in Patients with Normal Cardiac Function?

Abstract: Background: Whether right ventricular outflow tract (RVOT) pacing is superior to right ventricular apex (RVA) pacing in terms of ventricular synchrony, cardiac function, and remodeling in patients with normal cardiac function is still unknown. Hypothesis: Right ventricular outflow tract pacing is superior to RVA pacing in patients with normal cardiac function. Methods: A total of 96 consecutive patients with high or third-degree atrial ventricular block were enrolled and randomized into 2 groups: RVOT pacing g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 23 publications
1
66
0
1
Order By: Relevance
“…Previous investigations of alternative pacing sites have yielded inconsistent results (Mera et al, 1999;Giudici et al, 1997;Bourke et al, 2002;Victor et al, 2006;Kypta et al, 2008;Dabrowska-Kugacka et al, 2009;Tse et al Europace 2009;Victor et al, 1999) which may be attributable, in part, to the fact that the pacing site was determined on a topological rather than functional basis (Giudici & Karpawich, 1999). Many previous studies (Schwaab et al, 1999;Victor et al, 2006;Yu et al, 2007;Ng et al, 2009;Takemoto et al, 2009;Tse et al, Europace 2009, Gong et al, 2009Leong et al, 2010;Schwaab et al, 2001), have showed that septal pacing induced shorter paced QRS duration than RVA pacing did. These results indicated that RVS pacing resulted in better electric synchrony compared with RVA pacing.…”
Section: Electric and Mechanic LV Synchronymentioning
confidence: 96%
See 4 more Smart Citations
“…Previous investigations of alternative pacing sites have yielded inconsistent results (Mera et al, 1999;Giudici et al, 1997;Bourke et al, 2002;Victor et al, 2006;Kypta et al, 2008;Dabrowska-Kugacka et al, 2009;Tse et al Europace 2009;Victor et al, 1999) which may be attributable, in part, to the fact that the pacing site was determined on a topological rather than functional basis (Giudici & Karpawich, 1999). Many previous studies (Schwaab et al, 1999;Victor et al, 2006;Yu et al, 2007;Ng et al, 2009;Takemoto et al, 2009;Tse et al, Europace 2009, Gong et al, 2009Leong et al, 2010;Schwaab et al, 2001), have showed that septal pacing induced shorter paced QRS duration than RVA pacing did. These results indicated that RVS pacing resulted in better electric synchrony compared with RVA pacing.…”
Section: Electric and Mechanic LV Synchronymentioning
confidence: 96%
“…The RV septal pacing also resulted in shorter isovolumic relaxation than RV apical pacing (Yu et al, 2007), implicating better diastolic function that has been invasively demonstrated by Kolettis et al (Kolettis et al, 2000) at the cardiac catheterization laboratory. In fact despite the beneficial features of reducing electrical and mechanical dyssynchrony , different studies failed to demonstrate a positive effect on indices of LV structure and 85 function and did not confirm the above mentioned clinical outcomes, at least during the 3-18 months after implantation (Bourke et al, 2002;Victor et al, 2006;Kypta et al, 2008;Dabrowska-Kugacka et al, 2009;Gong et al, 2009;Cano et al, 2010) Kypta et al (Kypta et al, 2008) randomized 98 patients with atrioventricular block (AVblock) undergoing pacemaker implantation to positioning the ventricular lead in the high or mid septum (n =53) or in the apex (n = 45) of the right ventricle. The Changes of N-terminal pro-brain natriuetic peptide (BNP) levels, LVEF, and exercise capacity from baseline to 18 months were statistically not different between septal and apical stimulation.…”
Section: Authorsmentioning
confidence: 99%
See 3 more Smart Citations